1987
DOI: 10.1042/bj2420289
|View full text |Cite
|
Sign up to set email alerts
|

Rapid increases in inositol 1,4,5-trisphosphate, inositol 1,3,4,5-tetrakisphosphate and cytosolic free Ca2+ in agonist-stimulated pancreatic acini of the rat. Effect of carbachol, caerulein and secretin

Abstract: We compared the time course of increases in isomers of inositol trisphosphate [Ins(1,4,5)P3] and Ins(1,3,4)P3] and the tetrakisphosphate [Ins(1,3,4,5)P4] with changes in cytosolic free Ca2+ [( Ca2+]i) in dispersed pancreatic acini of the rat. There were rapid (5s) increases in Ins(1,4,5)P3 and Ins(1,3,4,5)P4 in response to carbachol, caerulein and secretin, whereas Ins(1,3,4)P3 increased more slowly. All three secretagogues induced increases in [Ca2+]i, which reached a peak at 15-20 s. Our results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…5) (compare also Irvine & Moor, 1986). It is therefore clear that Ins 1,3,4,5 P4, which is rapidly formed from Ins 1,4,5 P3 during receptor activation (Batty, Nahorski & Irvine, 1985;Hawkins, Stephens &Downes, 1986;Trimble et al, 1987), has a dramatic effect on cellular Ca 2+ handling since it transforms the transient Ca2+-activated K + current response evoked by Ins 1,4,5 P3 alone into a long sustained current increase (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…5) (compare also Irvine & Moor, 1986). It is therefore clear that Ins 1,3,4,5 P4, which is rapidly formed from Ins 1,4,5 P3 during receptor activation (Batty, Nahorski & Irvine, 1985;Hawkins, Stephens &Downes, 1986;Trimble et al, 1987), has a dramatic effect on cellular Ca 2+ handling since it transforms the transient Ca2+-activated K + current response evoked by Ins 1,4,5 P3 alone into a long sustained current increase (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this idea, we have shown that alkalinization of insulin granules by Ins(3,4,5,6) P 4 has the effect of reducing insulin secretion from pancreatic β-cells (Renström et al, 2002). This has previously led us (Renström et al, 2002) to consider what might be the pathological consequences of a persistently activated pancreatic Ins(3,4,5,6) P 4 signal, such as that which would inevitably (see Section 4) accompany sustained glucose-dependent activation of PLC (Trimble et al, 1987). Perhaps in some individuals, such abnormally elevated Ins(3,4,5,6) P 4 levels contribute to the hyperglycemia-dependent refractoriness of β-cells (Meyer et al, 2002) which typifies type 2 diabetes etiology (Kilpatrick and Robertson, 1998).…”
Section: Ins(3456)p4 Regulates Cl− Channel Conductancementioning
confidence: 99%
“…These results suggest that the effect of isoprenaline on DAG formation is mediated by a,-adrenoceptor activation, that it is not related to the increase in cyclic AMP, and that it is closely related to PIP2 hydrolysis. Various agonists cause phospholipase C-dependent phosphoinositide hydrolysis through the receptor-G pro tein system and stimulate the release of two putative sec ond messengers, inositol 1,4,5-phosphate (1,4,5-IP3) and sn-1,2-diacylglycerol (DAG) (1)(2)(3)(4)(5). DAG may activate a protein kinase C and thus play an important role in the process leading to exocytosis (6).…”
mentioning
confidence: 99%